Approaches to target tractability assessment – a practical perspective. Issue 4 (22nd February 2018) - Brown, Kristin K.; Hann, Michael M.; Lakdawala, Ami S.; Santos, Rita; Thomas, Pamela J.; Todd, Kieran
Abstract : The assessment of the suitability of novel targets to intervention by different modalities, e.g. small molecules or antibodies, is increasingly seen as important in helping to select the most progressable targets at the outset of a drug discovery project. Abstract : The assessment of the suitability of novel targets to intervention by different modalities, e.g. small molecules or antibodies, is increasingly seen as important in helping to select the most progressable targets at the outset of a drug discovery project. This perspective considers differing aspects of tractability and how it can be assessed using in silico and experimental approaches. We also share some of our experiences in using these approaches.